A new world mbira: the Caribbean marimbula - Thompson, Donald (International Library of African Music, 1975)
As is well known, many musical instruments of African origin have survived and flourished in America, in many cases becoming adapted to circumstances which differ widely from those surrounding the development and use of the prototypes. The mbira's appearance in the New World has occasionally been noted, in forms closely resembling the African types. However, little attention has been given to a peculiarly Caribbean form of the mbira or to the changes which have taken place in both the structure and the function of the transplanted instrument during its adaptation to a whole range of new social, musical and material circumstances.
Keywords: African Music